EVOLUTIONARY DYNAMICS OF AUTOPOLYPLOIDS IN NATURAL POPULATIONS: THE CASE OF TURNERA SIDOIDES COMPLEX - Kovalsky I.E.; Elías G.; Fernández S.A.; Moreno E.M.S.; Silva G.C.; Roggero Luque J.M.; Almirón N.E.A.; Solís C.; Dabrio A.; Via Do Pico G.M.; Seijo J.G.; Solís Neffa V.G. (BAG. Journal of Basic and Applied Genetics, 2022)
Turnera sidoides (x=7) is one of the few well-studied South American autopolyploid complexes. Since polyploidy has played a prominent role within this complex, ongoing studies in T. sidoides focus on understanding the mechanisms involved in the origin and the establishment of polyploids using integrative approaches. This paper synthesises the results of more than 20 years of research on this topic. Cytogenetics analysis provided evidences for the production of unreduced male and female gametes, supporting the hypothesis of bilateral sexual polyploidization as the mechanism of origin of polyploids in T. sidoides. The finding of viable triploids suggested that unilateral sexual polyploidization could also be an important mechanism for the origin of tetraploids in T. sidoides. The occurrence of plants continuously forming many unreduced gametes would play a key role in the establishment of neopolyploids in natural populations. Also, the higher number of propagules that tetraploids contribute to subsequent generations, the ability to multiply asexually by rhizomes, and the occurrence of occasional cases of self-compatibility and successful illegitimate crosses in polyploids increase the likelihood that a low frequency of neopolyploids can be maintained in natural populations of T. sidoides. In addition, integration of cytogeographic and genetic divergence data together with past niche modelling provided further insights supporting the hypothesis that historical climatic and geomorphological events provided favourable conditions for the establishment of autopolyploids, with the wider distribution of tetraploids of T. sidoides being the result of their range expansion.